Distributed Nash equilibrium seeking: A gossip-based algorithm - Salehisadaghiani, Farzad; Pavel, Lacra (Automatica (Oxford), 2016)
This paper presents an asynchronous gossip-based algorithm for finding a Nash equilibrium (NE) of a game in a distributed multi-player network. The algorithm is designed in such a way that players make decisions based on estimates of the other players’ actions obtained from local neighbors. Using a set of standard assumptions on the cost functions and communication graph, the paper proves almost sure convergence to a NE for diminishing step sizes. For constant step sizes an error bound on expected distance from a NE is established. The effectiveness of the proposed algorithm is demonstrated via simulation for both diminishing and constant step sizes.